A Technical and Economic Evaluation of Geosynthetic Rolled Erosion Control Products in Highway Drainage Channels. Issue 2 (1st January 2002) - Smith, J.L.; Bhatia, S.K.; Walowsky, D.; Lake, D.
Abstract : Historically, local village, town, and county highway departments have relied heavily on the use of stone fill and rock riprap to line highway drainage channels. These are often constructed without the benefit of design or the evaluation of alternatives, because they have always been done this way. In September 1999, the Munro Road reconstruction project was completed in Onondaga County, New York. As part of an erosion and sediment control demonstration project, the drainage portion of the project was redesigned using geosynthetic rolled erosion control products (RECPs) in lieu of stone fill and rock riprap on almost 1, 130 m of channel. The use of the RECPs saved approximately $95, 800 in construction costs and is expected to lower maintenance costs as well as provide long-term protection against erosion. The overall purpose of the project was to demonstrate to highway departments the functional and economical advantages of using RECPs for these applications. This paper summarizes the design, construction, and performance to date of seven of the ten different RECPs installed for the project.